Sistem Informasi Monitoring Kegiatan Pembelajaran Santri Berbasis Website Pada Pondok Pesantren Tahfidzul Qur’an Nurul Fatikhah - Mubarok Ali Makhzumi; Niki Ratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The purpose of this study is to make it easier for guardians of students to monitor students' learning activities at Islamic boarding schools and make it easier for Islamic boarding schools to record administrative data for students who still use manuals, so that there are no delays, errors, and errors in reporting. Tahfidzul Qur'an Nurul Fatikhah Islamic Boarding School was founded in 1996 by KH Ahmad Sahudi. Currently, several obstacles and shortcomings are found in the student learning monitoring system, including the administrative system which is still done manually, causing problems in managing payment data, student data, and rote. For problems in managing payment data, they still use books to enter data for students who make payments for Madrasah Diniyah Education or students who have deposited memorization. It is the same with the monthly payments for Islamic Boarding Schools, which currently still use paper. Although the process used today uses a computer / laptop, but only uses Microsoft office. The method used for the development of information systems using the waterfall model and using the programming language PHP, HTML and MySQL database.